The Concept of Nativism in Islamic Education and its Relation to Philosophy - Matnur Ritonga; Herwina Bahar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The research discusses the philosophy of nativism in Islamic education. It explores the interconnectedness of philosophy, educational theory, and educational practice, and delves into the concept of nativism, which suggests that individuals are significantly influenced by innate factors from birth. The research also touches on empiricism and convergence as alternative theories, and it examines the implications of nativism in the context of Islamic education. This research employs a Literature Review method, incorporating the Quranic verses and their exegesis, also hadis thematically to support the discussion. The research references various Quranic verses and their interpretations to support the Islamic perspective on the innate nature of humans and its alignment with religious inclinations. The result emphasizes the concept of fitrah in Islam, which denotes the innate disposition of humans and its role in understanding human potential. It also addresses the potential contradiction between nativism and common sense, highlighting the Islamic recognition of innate talent while emphasizing that such differences can still be developed.